INVESTIGATION OF THE ANTIRADICAL ACTIVITY OF THE ZIZIPHORA PLANT (ZIZIPHORA SPP.) - N. J. Masharipova (Modern American Journals, 2025)
In this study, the antiradical activity of ethanol extracts obtained from Ziziphora clinopodioides subsp. rigida was evaluated using the 2,2-diphenyl-1-picrylhydrazyl (DPPH) free radical scavenging assay. The influence of different volumes of the extract (25, 50, 75, and 100 μL) on the DPPH radical solution was examined spectrophotometrically at 517 nm. The absorbance reduction was used as a measure of free radical neutralization. The experimental data confirmed the extract’s significant antiradical potential, with an IC₅₀ value calculated at 99.62 μL, indicating moderate antioxidant efficiency. These findings suggest that Ziziphora clinopodioides may serve as a natural source of bioactive compounds with antioxidant properties, potentially useful in pharmaceutical or nutraceutical applications.
Keywords: Ziziphora, antiradical activity, DPPH, IC₅₀, spectrophotometry, ethanol extract, free radicals, natural antioxidants, phytochemicals, bioactive compounds.